2016
DOI: 10.18553/jmcp.2016.22.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Initiation of Novel Oral Anticoagulants in Medicare Beneficiaries

Abstract: BACKGROUND As alternatives to warfarin, 2 novel oral anticoagulants (NOACs), dabigatran and rivaroxaban, were approved in 2010 and 2011 to prevent stroke and other thromboembolic events in patients with atrial fibrillation. It is unclear how patient characteristics are associated with the initiation of anticoagulants. OBJECTIVE To evaluate how patient demographics, clinical characteristics, types of insurance, and patient out-of-pocket spending affect the initiation of warfarin and 2 NOACs—dabigatran and riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 13 publications
2
31
1
Order By: Relevance
“…described patient characteristics and demographics amongst initiators of dabigatran and rivaroxaban compared with warfarin for stroke prophylaxis in AF. Patients who had suffered from stroke, kidney disease, acute myocardial infarction (only for dabigatran) or congestive heart failure had lower odds of being initiated on either dabigatran or rivaroxaban compared with warfarin . Desai et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…described patient characteristics and demographics amongst initiators of dabigatran and rivaroxaban compared with warfarin for stroke prophylaxis in AF. Patients who had suffered from stroke, kidney disease, acute myocardial infarction (only for dabigatran) or congestive heart failure had lower odds of being initiated on either dabigatran or rivaroxaban compared with warfarin . Desai et al .…”
Section: Discussionmentioning
confidence: 99%
“…Baik et al described patient characteristics and demographics amongst initiators of dabigatran and rivaroxaban compared with warfarin for stroke prophylaxis in AF. Patients who had suffered from stroke, kidney disease, acute myocardial infarction (only for dabigatran) or congestive heart failure had lower odds of being initiated on either dabigatran or rivaroxaban compared with warfarin [20]. Desai et al [18] found lower odds of initiation of one of the NOACs compared with warfarin in patients who suffered from congestive heart failure, diabetes, stroke, previous bleeding or renal dysfunction.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…3 Then, we estimated the average probability of receiving oral anticoagulation and the average probability of being prescribed an NOAC among patients on oral anticoagulation in each HRR, while holding all predictors mentioned above constant. 6 This methodology enabled us to isolate geographic variation that is not explained by the confounders listed above.…”
Section: August 2017mentioning
confidence: 99%
“…2 After new oral anticoagulants (NOACs) had entered the market, several studies evaluated the factors associated with the initiation of NOACs, relative to warfarin. 3 However, it remains unclear how the use of oral anticoagulation in AF varies across regions of the United States. To address this question, we used 2013 to 2014 claims data from a 5% random sample of Medicare beneficiaries.…”
mentioning
confidence: 99%
“…Physicians also report clinical characteristics of the patient, risk of adverse events, their own knowledge, experience and preferences to be important in decision‐making. Database studies have identified mainly clinical factors, such as estimated stroke risk, age and other cardiovascular diseases as factors affecting the choice of an OAC. These studies have also found lower socio‐economic status and poorer medication coverage to favour the use of VKAs.…”
Section: Introductionmentioning
confidence: 99%